“Methanoplasmatales,” Thermoplasmatales-Related Archaea in Termite Guts and Other Environments, Are the Seventh Order of Methanogens - Paul, Kristina (American Society for Microbiology, 2012)
The Euryarchaeota comprise both methanogenic and nonmethanogenic orders and many lineages of uncultivated archaea with unknown properties. One of these deep-branching lineages, distantly related to the Thermoplasmatales, has been discovered in various environments, including marine habitats, soil, and also the intestinal tracts of termites and mammals. By comparative phylogenetic analysis, we connected this lineage of 16S rRNA genes to a large clade of unknown mcrA gene sequences, a functional marker for methanogenesis, obtained from the same habitats. The identical topologies of 16S rRNA and mcrA gene trees and the perfect congruence of all branches, including several novel groups that we obtained from the guts of termites and cockroaches, strongly suggested that they stem from the same microorganisms. This was further corroborated by two highly enriched cultures of closely related methanogens from the guts of a higher termite (Cubitermes ugandensis) and a millipede (Anadenobolus sp.), which represented one of the arthropod-specific clusters in the respective trees. Numerous other pairs of habitat-specific sequence clusters were obtained from the guts of other termites and cockroaches but were also found in previously published data sets from the intestinal tracts of mammals (e.g., rumen cluster C) and other environments. Together with the recently described Methanomassiliicoccus luminyensis isolated from human feces, which falls into rice cluster III, the results of our study strongly support the idea that the entire clade of “uncultured Thermoplasmatales” in fact represents the seventh order of methanogenic archaea, for which the provisional name “Methanoplasmatales” is proposed.